2017
DOI: 10.15690/vramn756
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Metatarsalgia: Pathogenesis, Biomechanics and Surgical Treatment

Abstract: This paper presents a comprehensive review on the current concept of the diagnosis and treatment of central metatarsalgia on the basis of medical literature analyses. Metatarsalgia is the term for pain in the forefoot. This is a set of symptoms corresponding to a wide range of diseases. Central metatarsalgia is a kind of metatarsalgia which arises from structural-functional changes that lead to excessive pressure in the area of metatarsal heads. The data analysis demonstrated that presently various types of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…These changes occur as a result of the metatarsal head being translated proximally, the metatarsals undergoing shortening and elevation, and the surrounding soft tissues being disrupted. 12 , 27 , 28 Nevertheless, inadequate attention was given to the treatment of ligaments and tendons during the surgical procedure, resulting in a lack of tension in these structures (Figure 4 ). This particularly affected the flexor tendon, impeding its ability to fulfill its usual function of exerting pulling force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes occur as a result of the metatarsal head being translated proximally, the metatarsals undergoing shortening and elevation, and the surrounding soft tissues being disrupted. 12 , 27 , 28 Nevertheless, inadequate attention was given to the treatment of ligaments and tendons during the surgical procedure, resulting in a lack of tension in these structures (Figure 4 ). This particularly affected the flexor tendon, impeding its ability to fulfill its usual function of exerting pulling force.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has indicated that following the Weil osteotomy procedure, there are alterations in the positioning of the ligaments and tendons (specifically, the flexor tendon and extensor tendon) in the foot. These changes occur as a result of the metatarsal head being translated proximally, the metatarsals undergoing shortening and elevation, and the surrounding soft tissues being disrupted 12,27,28 . Nevertheless, inadequate attention was given to the treatment of ligaments and tendons during the surgical procedure, resulting in a lack of tension in these structures (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The increasingly performed minimally invasive procedures were designed to reduce this problem. The evidence in the direct comparison of Weil osteotomy and DMMO is sparse and inadequate; furthermore, an unsatisfactory incidence of floating toes of sometimes 30% or more remains with both procedures [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Необходимо оценить гибкость и величину данной деформации, а также стабильность плюснефалангового сустава. При осмотре необходимо также обратить внимание на сопутствующие деформации стопы и метатарзалгию [15], что помогает определить тактику дальнейшего лечения.…”
Section: молоткообразная деформация пальцев: диагностика и методы хирургической коррекцииunclassified